Macropores and preferential flow—a love‐hate relationship. Issue 1 (11th December 2016) - Weiler, Markus
Abstract: Preferential flow is of high relevance for runoff generation, transport of chemicals and nutrients, and the transit time distribution of water in the soil or watershed. However, preferential flow effects are generally ignored in lumped hydrological models. And even most physically‐based models ignore macropores and preferential flow features at the soil and hillslope scale. Keith Beven was never satisfied with this situation and he tried again and again to convince the scientific community to focus their research on the complex topic of macropore and preferential flow. Although he recognized how difficult it is to correctly include preferential flow in hydrological models, he made substantial progress defining and describing macropore flow and showing its relevance, developing models to simulate preferential flow, and in particular, the interaction between macropores and the soil matrix. In this short commentary, I reflect on these achievements and outline a vision for research in preferential flow experiments and modeling.